Enhancing group cognitive‐behavioral therapy for hoarding disorder with between‐session Internet‐based clinician support: A feasibility study. Issue 7 (7th February 2018) - Ivanov, Volen Z.; Enander, Jesper; Mataix‐Cols, David; Serlachius, Eva; Månsson, Kristoffer N.T.; Andersson, Gerhard; Flygare, Oskar; Tolin, David; Rück, Christian
Abstract: Objective: Hoarding disorder (HD) is difficult to treat. In an effort to increase efficacy and engagement in cognitive‐behavioral therapy (CBT), we developed and evaluated a novel intervention comprising group CBT combined with between‐session Internet‐based clinician support for people with HD. Method: Twenty participants with HD received group CBT combined with an Internet‐support system enabling therapist–participant communication between group sessions. Results: The treatment was associated with a significant reduction on the Saving Inventory—Revised (SI‐R) and a large effect size (Cohen's d  = 1.57) was found at posttreatment. Treatment gains were maintained at the 3‐month follow‐up. Group attendance was high and no participants dropped out from treatment prematurely. Between‐session motivational support from the therapist was most frequently mentioned as the main strength of the system. Conclusion: The results of this study support adding Internet‐based clinician support to group CBT for HD to increase treatment adherence and, potentially, improve the overall efficacy of CBT.